Accurate characterization of wildlife trade and policy instruments: reply to D'Cruze et al. (2022) and Frank and Wilcove (2022) - Challender, D; Brockington, D; Hinsley, A; 't Sas-Rolfes, M; Milner-Gulland, EJ (Wiley Open Access, 2022)
D'Cruze et al. (2022) and Frank and Wilcove (2022) suggest that Challender et al. (2021) misrepresent their research. We reiterate that our intention was not to denigrate any particular study; instead, we aimed to draw attention to contemporary issues in wildlife trade research and highlight ways for research to better inform policy processes. Here, we respond to the points raised in these articles.